A randomised pilot study to assess the efficacy of an interactive, multimedia tool of cognitive stimulation in Alzheimer's disease. Issue 10 (4th July 2006) - Tárraga, L; Boada, M; Modinos, G; Espinosa, A; Diego, S; Morera, A; Guitart, M; Balcells, J; López, O L; Becker, J T
Abstract : Objective: To determine the usefulness of an interactive multimedia internet-based system (IMIS) for the cognitive stimulation of Alzheimer's disease. Methods: This is a 24-week, single-blind, randomised pilot study conducted on 46 mildly impaired patients suspected of having Alzheimer's disease receiving stable treatment with cholinesterase inhibitors (ChEIs). The patients were divided into three groups: (1) those who received 3 weekly, 20-min sessions of IMIS in addition to 8 h/day of an integrated psychostimulation program (IPP); (2) those who received only IPP sessions; and (3) those who received only ChEI treatment. The primary outcome measure was the Alzheimer's Disease Assessment Scale-Cognitive (ADAS-Cog). Secondary outcome measures were: Mini-Mental State Examination (MMSE), Syndrom Kurztest, Boston Naming Test, Verbal Fluency, and the Rivermead Behavioral Memory Test story recall subtest. Results: After 12 weeks, the patients treated with both IMIS and IPP had improved outcome scores on the ADAS-Cog and MMSE, which was maintained through 24 weeks of follow-up. The patients treated with IPP alone had better outcome than those treated with ChEIs alone, but the effects were attenuated after 24 weeks. All patients had improved scores in all of the IMIS individual tasks, attaining higher levels of difficulty in all cases. Conclusion: Although both the IPP and IMIS improved cognition in patients with Alzheimer's disease, the IMIS program provided an improvement above and beyond that seen with IPP alone, which lasted for 24 weeks.